PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN GREEN ACCOUNTING TERHADAP FINANCIAL DISTRESS (Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2023-2024) - Khansa Aira Meytasari; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2026)
The study aims to examine the impact of Corporate Social Responsibility (CSR) and green accounting on financial distress. The dependent variable in this study is financial distress, measured using the modified Altman Z-score. The independent variables used in this study are Corporate Social Responsibility (CSR), measured using the Global Reporting Initiative (GRI) 2021, and green accounting, measured using the PROPER rating.The population of this study is all manufacturing companies listed in Indonesia Stock Exchange (IDX) during 2023-2024. The sampling method used in this study was purposive sampling, with a total sample size of 56 companies. The data used in this study are secondary data obtained from the annual reports and financial statements of the manufacturing companies. The analytical method used in this study is multiple linear regression.The results of this study show that Corporate Social Responsibility (CSR) has a significant negative effect on financial distress. However, green accounting has an insignificant positive effect on financial distress.